Gambaran Perilaku Hygiene Sanitasi Pedagang Makanan Jajanan di Jakabaring Sport City Kota Palembang Tahun 2025 - Cantika Maharani Prastianti; Diah Navianti; Kamsul Kamsul (Vitamin : Jurnal ilmu Kesehatan Umum, 2026)
Food safety is an important issue in the prevention of food-borne diseases because contaminated food can cause diseases such as diarrhea, typhoid fever, and food poisoning. Snack food vendors, as direct food handlers, have an important role in maintaining food hygiene and sanitation. Research Objective: To know the description of the sanitary hygiene behavior of snack food vendors in Jakabaring Sport City, Palembang City in 2025. Research Methods: This type of research is descriptive research. The population in this study is all snack food traders around the Jakabaring Sport City lake, Palembang City. The sample in this study was 36 people. The data collection tool is the questionnaire sheet. Data analysis was carriedout by univariate analysis. Research Results: The results of this study show that the characteristics of respondents based on gender are male (25.0%) and female (75.0%), young age < 47 years old (41.5%) and old age ≥ 47 years old (51.8%), the last education of elementary and junior high school is (52.8%) and high school-college (47.2%). Respondents' knowledge was not good (66.7%) and good (33.3%),respondents' attitudes were negative (36.1%) and positive (63.9%), respondents' actions were not good (55.6%) and good (44.4%). Conclusion: Although most traders have a positive attitude towards sanitation hygiene, the low knowledge and inappropriate actions indicate the need for regular education and supervision efforts to improve sanitation hygiene behavior among snack food traders.